A trio of case reports - Chirarelli, Catherine (Canadian Journal of Optometry, 2026)
Optometrists are often called upon to evaluate children with learning disabilities, to provide a diagnosis and to make recommendations concerning their visual function. Many factors must be considered in the examination of such children, including any anomalies of refraction, binocularity and perception which must be identified. The impact of such anomalies on reading performance and the benefit of visual remediation have been sources of controversy in recent years. This case report illustrates the interaction of several different factors (visual, intellectual and academic) and the value of optometric therapy as part of a multidisciplinary approach to treating learning disabilities.